Global hotspots and trends in gut mycological research: a visual analytics and bibliometric approach - Zhu, Wenhao; Chi, Jiayu; Zhang, Yongde; Wu, Dongliang; Xia, Xinyu; Liao, Xingyu; Xu, Kexin; Shi, Wenying; Hu, Haowen; Wang, Wei; Lu, Zhiyuan; Zhang, Zixu; et al. (Frontiers in Immunology, 2024)
Background: Recent findings highlight the significant impact of intestinal fungi on the complex makeup of the gut microbiota and human health, challenging past oversights. However, a lack of thorough systematic and quantitative analyses remains. This study aims to address this gap by thoroughly examining the current research on gut fungi. Through analyzing developments and unique features in this area, our goal is to foster a deeper understanding and identify future research pathways.Methods: We performed an extensive bibliometric analysis on documents from 2000 to 2023, sourced from the Web of Science Core Collection (WoSCC). Utilizing advanced visualization tools such as VOSviewer, CiteSpace, and Bibliometrix R, we meticulously examined and illustrated the data in scientific landscapes and networks.Results: A total of 1434 papers were analyzed, revealing a substantial increase in publication volume over the past two decades, particularly in 2020.Contributions came from 67 countries, 2178 institutions, and 8,479 authors.China led in publication output with 468 articles, followed by the University of California with 84 articles, and ZHANG F as the most prolific author with 17 articles. Emerging research areas such as "Fungal-Bacteria Interactions," "Gut Fungus and Gut-Brain Axis," and "Gut Fungus and Immunity" are expected to attract growing interest in the future.This extensive bibliometric analysis offers a current overview of scholarly efforts concerning intestinal fungi, highlighting the predominant landscape in this field. These insights can assist scholars in identifying appropriate publication avenues, forming collaborative relationships, and enhancing understanding of key themes and emerging areas, thereby stimulating future research endeavors.